2014
DOI: 10.1155/2014/307317
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Unit Admission after Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy. Is It Necessary?

Abstract: Introduction. Cytoreductive surgery (CS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is a new approach for peritoneal carcinomatosis. However, high rates of complications are associated with CS and HIPEC due to treatment complexity; that is why some patients need stabilization and surveillance for complications in the intensive care unit. Objective. This study analyzed that ICU stay is necessary after HIPEC. Methods. 39 patients with peritoneal carcinomatosis were treated according to strict selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Previous studies reported a higher percentage (67%-100%) of patients admitted to the ICU postoperatively[22,28,29]. The mean ICU LOS in this patient population was also similar to the previous studies (≤ 5 d)[6,29].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies reported a higher percentage (67%-100%) of patients admitted to the ICU postoperatively[22,28,29]. The mean ICU LOS in this patient population was also similar to the previous studies (≤ 5 d)[6,29].…”
Section: Discussionsupporting
confidence: 88%
“…However, it was recently reported that there was no difference in the rate and degree of complications observed in patients who were admitted in the ICU, noting that ICU admission should not be standardized, but based on individual patient characteristics. [22] Intraoperative parameters may be associated with postoperative outcome, in terms of morbidity and mortality, as demonstrated by a previous study conducted by our team. [23] 4.3 Lactate as a marker of perioperative and long -term outcome…”
Section: Lactate Physiology and Hyperlactaemiamentioning
confidence: 60%
“…However, it was recently reported that there was no difference in the rate and degree of complications observed in patients who were admitted to the ICU, noting that ICU admission should not be standardized but should be based on individual patient characteristics [8]. …”
Section: Discussionmentioning
confidence: 99%